La importància històrica de les cròniques de la guerra de las Alpujarras: estudi comparatiu de la batalla de Frigiliana. - JURADO RIBA, VÍCTOR (Scripta)
The Moorish rebellion of Las Alpujarras (1568-1571) is a well-known conflict, but not only because of the efforts of historiography, especially Andalusian. The role of chroniclers is crucial in establishing facts, especially because of the historical will of the texts and their presence on the battlefield, as demonstrated by those who have studied their biographies. In this paper we will go further: we will take the battle of the rock of Frigiliana as a central element and will face the correspondence of the leaders and the narrations in the chronicles, analysing the various elements of the confrontation and calibrating their accuracy and even how they offer some more plausible information than Lluís de Requesens himself.